Pengaruh Influencer Marketing dan Value Co-Creation terhadap Customer Engagement melalui Minat Beli dan Impulsive Buying pada Fashion Batik Modern Kartini’s Label (Studi kasus pada Generasi Z dan Generasi Milenial di Jawa Barat) - Sita Sopiana; Ade Komaludin; Edy Suroso (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to examine the direct influence of influencer marketing and value co-creation on customer engagement through two intervening variables, namely purchase intention and impulsive buying. An empirical investigation was conducted among consumers of Batik Kartini's Label fashion, specifically targeting Generation Z and Millennials in West Java. The sample was collected using stratified random sampling, resulting in 210 female respondents who have made at least one purchase. The research instrument employed was a questionnaire featuring Likert scale statements. Data analysis was performed using Structural Equation Modelling with the Smart PLS application. The findings reveal that: 1) Influencer marketing and value co-creation positively impact purchase intention; 2) These strategies also enhance impulsive buying; 3) Both factors contribute to higher customer engagement; 4) Purchase intention and impulsive buying drive increased customer engagement; 5) Influencer marketing boosts customer engagement through purchase intention; 6) Influencer marketing enhances customer engagement via impulsive buying; 7) Value co-creation strengthens customer engagement through purchase intention; and 8) Value co-creation improves customer engagement via impulsive buying.